PENGARUH RASIO CAMEL TERHADAP PERTUMBUHAN LABA (Studi pada Bank GO Publik yang Terdaftar di BEI Periode 2007 â 2010) - Purnomo, SE., M.Si, Djauhar Edi (Majalah Neraca, 2012)
This research aims to examine the influence of CAMEL ratios with earnings growth. Ratios that was applied in this research are : CAR, NPL, NPM, BO/PO and LDR.The population in this research are all of banking firsm listed in Indonesian stock Exchange 2007 â 2010. Total sample in this research are 23 banking firms that selected with purposive sampling. Independent variable in this research are : CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), NPM (Net Profit Margin), BO/PO (Operational Expenses to Operational Revenue), LDR (Loan to Deposit Ratio). Dependent variable in this research is earning growth. Data analyzed with classic assumption test and hypothetical testing with multiple regression models.The results of this research indicates that NPM and LDR variable had positive influence to earning growth. BO/PO variable had negative influence to earning growth. CAR and NPL variable had not influence to earning growth. Keywords : CAMEL Ratios, earning growth.